Flipped Classroom Learning Model With Kahoot Media: the Effectiveness to Affect Students Motivation and Learning Outcomes in Biology Subject - Diana Zulyetti (CV. Pusdikra Mitra Jaya, 2023)
The problem of low motivation and student learning outcomes in Biology after the Covid-19 pandemic is still found at SMAN 1 Payakumbuh District. In this study a flipped classroom type hybrid learning model was used combined with the use of the kahoot! game application. The research was conducted using a quasi-experimental quantitative approach with a one shot case study design in class XI MIPA 1 students totaling 32 people. Data were collected using motivational questionnaires and objective questions to measure student learning outcomes. The results of the study show the use of the flipped classroom type hybrid learning model combined with the use of the kahoot! effective effect on increasing motivation and student learning outcomes in Biology subject, besides that the use of this model also has a positive effect on student independence in learning.